PROFESIONALISME KERJA PERANGKAT KELURAHAN DALAM PELAYANAN ADMINISTRASI PADA MASYARAKAT DI KANTOR KELURAHAN TALIKURAN BARAT KECAMATAN KAWANGKOAN UTARA - RUNKAT, REZA; DENGO, SALMIN; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2021)
In this study, the aim of this study was to find out how the professionalism of the village apparatus worksin administrative services for the community at the West Talikuran Village Office, North KawangkoanDistrict. This study used descriptive qualitative method. The theory used in this study is the theory ofindicators of work professionalism from Mertin Jr. which includes proficiency in using tools, readiness,responsibility in service, discipline and employee attitudes. The research informants were village officialsand the community as recipients of administrative services, totaling 9 people. Data collection techniquesthat researchers use are observation, interviews, and documentation. Based on the findings of the researchconducted, it can be concluded that the professionalism of the village apparatus in administrative servicesfor the community at the West Talikuran Village Office, North Kawangkoan District can be said to be quitegood even though it has not fully worked professionally because there are indicators that have not beencarried out properly such as proficiency in using tools so that lack of employee skills in administrativeservices, lack of employees so that the organizational structure has not been filled, and employee disciplinethat must be improved again. So in conclusion, the professionalism of the village apparatus must beconsidered and improved in order to produce a better quality of administrative services.Keywords: Work Professionalism, Village Apparatus, Administrative Services.